РОЗГОРТАННЯ АТЕЇСТИЧНОЇ РОБОТИ НА ПІДПРИЄМСТВАХ ПІВДНЯ УКРАЇНИ У 20-ті – 30-ті рр. ХХ ст. (Zaporizhzhia Historical Review, 2021)
The author characterized the social factors that had an influence on the functioning of the religious press. The role of the state and the ruling party in the closing of the magazines was determined.